2017
DOI: 10.1002/14651858.cd004455.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis for operative vaginal delivery

Abstract: One small trial was identified reporting only two outcomes. Evidence from this single trial suggests that antibiotic prophylaxis may lead to little or no difference in endometritis or maternal length of stay. There were no data on any other outcomes to evaluate the impact of antibiotic prophylaxis after operative vaginal delivery. Future research on antibiotic prophylaxis for operative vaginal delivery is needed to conclude whether it is useful for reducing postpartum morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…First, before pregnancy, it is suggested that women of child‐bearing age strengthen physical exercise, pay attention to nutritional regulation, actively prevent and control the reproductive system diseases, especially inflammatory diseases, reduce the frequency of uterine curettage, and make good preparation for pregnancy . During pregnancy, it is suggested that early pregnancy be determined in time, health management during pregnancy be actively implemented, the standard maternal manual be created before 13 weeks of gestation, the comprehensive physical examination be given, and high‐risk pregnancy and pathologic pregnancy be screened to improve the safety of pregnancy. During delivery, sterile operations should be strictly performed, the digital anal examination is strictly forbidden, the frequency of vaginal examination should be reduced as far as possible to reduce the incidence rate of retrograde infection, indications of cesarean section and lateral episiotomy should be strictly grasped, antibacterial drugs can be used for a short time for those undergoing cesarean section to prevent the infection, and the maternal management should be strengthened to improve the hospital delivery rate, prevent postpartum hemorrhage, and reduce the injury of birth canal due to delivery as far as possible .…”
Section: Discussionmentioning
confidence: 99%
“…First, before pregnancy, it is suggested that women of child‐bearing age strengthen physical exercise, pay attention to nutritional regulation, actively prevent and control the reproductive system diseases, especially inflammatory diseases, reduce the frequency of uterine curettage, and make good preparation for pregnancy . During pregnancy, it is suggested that early pregnancy be determined in time, health management during pregnancy be actively implemented, the standard maternal manual be created before 13 weeks of gestation, the comprehensive physical examination be given, and high‐risk pregnancy and pathologic pregnancy be screened to improve the safety of pregnancy. During delivery, sterile operations should be strictly performed, the digital anal examination is strictly forbidden, the frequency of vaginal examination should be reduced as far as possible to reduce the incidence rate of retrograde infection, indications of cesarean section and lateral episiotomy should be strictly grasped, antibacterial drugs can be used for a short time for those undergoing cesarean section to prevent the infection, and the maternal management should be strengthened to improve the hospital delivery rate, prevent postpartum hemorrhage, and reduce the injury of birth canal due to delivery as far as possible .…”
Section: Discussionmentioning
confidence: 99%
“…Presentations of the data from the NIHR programme studies 3,[7][8][9] at national meetings clearly showed that the natural response of the clinical community is to introduce prophylactic management with antibiotics, without clear evidence for the effectiveness of this approach following operative birth, because antibiotic prophylaxis been shown to be effective in reducing the risk of infection following caesarean birth. 10 Giving antibiotic prophylaxis after operative vaginal birth has thus been introduced into local guidance unsupported by evidence. Although similar in some ways, there are clear differences between the wound sites and potential contaminating organisms at caesarean section and instrumental birth, so it cannot be assumed that single-dose prophylactic antibiotics will be equally effective in both circumstances.…”
Section: Fundingmentioning
confidence: 99%
“…Twelve per cent of women in the UK undergo forceps or ventouse deliveries, 13 which is an estimated 90,000 women annually. The conservatively estimated incidence of maternal infection following operative vaginal birth is 4%, based on the one previous trial, 10 which results in an estimated 3600 women potentially having an infection after instrumental vaginal birth. Of these women, around 200 will be diagnosed with severe infection 7 and up to four may die from their infection.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted both in the UK and US have documented an additional risk associated with operative vaginal delivery [ 3 , 7 – 9 ]. A Cochrane review identified only one small previous trial of prophylactic antibiotics following operative vaginal delivery, which included a total of 393 women, with a relative risk of 0.07 (95% confidence interval 0.00 to 1.21) for postpartum infection [ 10 ]. Given the small study size and extreme result, the World Health Organisation (WHO) recommends that prophylactic antibiotics following operative vaginal delivery should not be used routinely and that further robust evidence is needed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%